Fungi associated with necrosis of vascular bundles in organic banana crop: symptoms, isolation and identification, and integrated management alternatives - Aguilar-Anccota, René (2021)
The banana Musa spp. (Musaceae) is a tropical perennial crop of major consumption in the world, the main producing regions are; Asia (54.1%), America (25.5%), Africa (18.4%). In Peru, Piura accounts for 72% of the country's total volume of organic banana exports. In recent years in Peru and in other producing areas of the world, symptoms of necrosis in the vascular bundles of the pseudostem have been occurring, causing the early death of plants in production. The objective of this study was to identify the main fungal pathogens associated with vascular necrosis of banana. The fungi isolated from the pseudostem, rhizome and roots were identified using taxonomic keys. The external symptoms of the disease were yellowing and necrosis of the leaves from the edge towards the midrib, collapse of the petiole and death of the plant. The internal symptoms were necrosis of the vascular bundles and internal necrotic lesions in the rhizome and roots. The fungal isolates were identified by their morphometric characteristics as Fusarium oxysporum, F. verticillioides and F. solani. For the control of this disease, it is recommended to implement an integrated management plan.